ChemInform Abstract: Utilizing Mor‐DalPhos/Palladium‐Catalyzed Monoarylation in the Multicomponent One‐Pot Synthesis of Indoles. Issue 22 (15th May 2015) - Rotta‐Loria, Nicolas L.; Borzenko, Andrey; Alsabeh, Pamela G.; Lavery, Christopher B.; Stradiotto, Mark
Abstract: Two classes of transformation, Buchwald—Hartwig amination and ketone mono‐α‐arylation, are combined to an one‐pot, multicomponent protocol in an inert atmosphere in presence of a diadamantyl‐phosphorus catalyst.